2007
DOI: 10.1029/2007jd008525
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of reservoir influences on annual and seasonal streamflow changes for the Lena, Yenisei, and Ob' rivers

Abstract: Since the 1930s, combined streamflow from the largest Eurasian rivers discharging to the Arctic Ocean has been increasing. For many of these rivers, an increase in annual streamflow volume has been accompanied by a shift in seasonality (e.g., earlier snowmelt runoff in the spring). These changes in annual and seasonal streamflow may be due to direct effects of climate change (e.g., increased precipitation, or changes in snow accumulation and ablation patterns), indirect effects of climate change (e.g., changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 57 publications
6
125
1
Order By: Relevance
“…Local anthropogenic water-use changes, for instance the construction and use of dams, may also influence the runoff and complicate the assessment of precipitation-runoff relations (Shibuo et al 2007;Adam et al 2007;Rawlins et al 2009b;Shiklomanov and Lammers 2009), although the effect of dams on annual discharge in the Arctic is generally small over longer time periods . In the Churchill basin, however, large-scale diversions of water out of the basin have strongly influenced the river flow (Déry et al 2005), yielding a considerably greater decrease in runoff than in precipitation over the studied period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local anthropogenic water-use changes, for instance the construction and use of dams, may also influence the runoff and complicate the assessment of precipitation-runoff relations (Shibuo et al 2007;Adam et al 2007;Rawlins et al 2009b;Shiklomanov and Lammers 2009), although the effect of dams on annual discharge in the Arctic is generally small over longer time periods . In the Churchill basin, however, large-scale diversions of water out of the basin have strongly influenced the river flow (Déry et al 2005), yielding a considerably greater decrease in runoff than in precipitation over the studied period.…”
Section: Discussionmentioning
confidence: 99%
“…For all basins, only years with complete runoff data for all months of the year were included. We have not corrected for the influence of dams in our analysis, as their effect on annual discharge trends over longer time periods has been shown to be relatively insignificant Adam et al 2007;Shiklomanov and Lammers 2009). …”
Section: Methodsmentioning
confidence: 99%
“…4 and 5). In this study, however, only the impact on long-term averaged discharge was analyzed, while possible seasonal impacts, e.g., due to reservoir operation, were not considered (Adam et al, 2007;Döll et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The VIC model has been widely used at global scale in many previous studies and has been demonstrated to capture the hydrology of different regimes well (Nijssen et al, 1997(Nijssen et al, , 2001aMaurer et al, 2002;Adam et al, 2007). The VIC model has also been used to successfully simulate and reconstruct hydrologic extremes such as drought and floods globally Sheffield and Wood, 2008a,b;Voisin et al, 2011;Wang et al, 2011).…”
Section: The Variable Infiltration Capacity (Vic) Modelmentioning
confidence: 99%